Priming and lexical interference in infancy - Styles, Suzy J. (2014)
Three experiments investigate priming effects in a looking task for infants in their second year. Infants hear two words (prime, target) in quick succession (separated by 200ms), and are presented with a picture pair (target, distracter) for 2500ms of free looking. Prime-target pairs are semantically and associatively related half of the time. Eye-movements are monitored. Infants aged 18- (Experiments 1, 2 and 3), 21- (Experiment 3) and 24- (Experiments 1 & 2) months were tested (N=328). 18-month-olds show consistent interest in named targets, but no priming effects. Experiment 1 demonstrates priming for 24-month-olds. Experiments 2 and 3 attempt to clarify whether this priming is fundamentally lexical (word-word) or visually mediated (word-picture), by varying the cue validity of the target as well as the prime. In Experiment 3, phonological competition produces a pattern of lexical interference and primed facilitation in 21-month-olds. This result supports a model of lexicon connectivity during the early stages of linguistic development.